Circularly Polarized Suspended Patch Antenna Fed by Modified L-Probe for UHF RFID Reader - K. S. Cheng (Radioengineering, 2017)
Two reader antennas, which are designed using the L-probe-fed suspended patch, are designed for the UHF band. To generate circular polarization, the L-shaped probe is modified by including an extra bend to provide one more degree of tuning freedom to the reflection coefficient without affecting the axial-ratio performance much. The proposed single-element reader antenna is able to achieve a CP bandwidth of 5.5 % (890 MHz - 940 MHz) and a maximum antenna gain of 9.7 dBi. When designed into a 2x2 array, the proposed reader antenna is able to produce CP bandwidth of 5.3 % (910 MHz - 960 MHz) with an antenna gain of 14.7 dBi. The read ranges of the proposed antenna and its array are 6.3 m and 10.9 m, respectively.